Influence of penicillin allergy on antibiotic prescribing patterns and costs - Irawati, Lyna (Curtin University, 2003)
The first part of this research was undertaken to assess the impact of documented penicillin allergy on the choice of antibiotics and the clinical and financial consequences of changes in prescribing patterns in an Australian teaching hospital. The medical records of all patients aged >/= 18 years admitted with community-acquired pneumonia (CAP) to Sir Charles Gairdner Hospital (SGGH) over a 15-week period were reviewed prospectively. The severity of patients' penicillin allergies was assessed using a structured questionnaire. The antibiotic cost was calculated using acquisition, delivery (labour and equipment) and laboratory monitoring costs. The appropriateness of antibiotic prescribing was assessed using the Therapeutic Guidelines: Antibiotic (TG:A). The antimicrobial selections and costs were then compared for those patients with (Group A) and without (Group B) penicillin allergy. 155 patients were reviewed (males 71, females 84) with an average age of 68 ± 18 years. Of these, 27 (17.4%) had documented penicillin allergies; of which 12 were classified as Severity I (e.g. anaphylaxis, urticaria), 12 as Severity II (e.g. rash, itch) and three as intolerance (e.g. GI upset). The current TG:A recommends cephalothin or cephazolin as the drugs of choice for mild to moderate CAP patients with a history of penicillin allergy. However, combinations of cephalothin intravenously and azithromycin orally were the most commonly prescribed antimicrobials for such patients. The TG:A recommends erythromycin plus cefotaxime or ceftriaxone as the first-line therapy for severe CAP patients with a documented penicillin allergy. Yet, combinations of intravenous cephalothin, erythromycin and gentamicin were the most frequently prescribed antimicrobials for such patients.A history of penicillin allergy significantly (p<0.05) increased the cost of antibiotic treatment and total cost of admission. The adherence of antibiotic prescribing to the TG:A for patients with penicillin allergies is variable. Patients with labelled penicillin allergies had greater antibiotic costs and total cost of admission. Identifying patients with intolerance rather than allergies would reduce the total inpatient costs at SCGH by A$ 463.01 a year for mild to moderate CAP patients and A$ 39 614.54 a year for severe CAP patients. The second part of the project was a prospective study of patients admitted to SCGH who had a history of penicillin allergy, but were not suffering from CAP. This study was conducted in order to ensure that the pattern of penicillin allergies of patients admitted to the hospital could be adequately characterised. Over a 5-week period, all adult patients admitted without CAP to SCGH who claimed to have a history of penicillin allergy were interviewed with regard to their penicillin allergies. The standard of allergy documentation was also assessed for each patient. Of the 140 patients assessed (males 63, females 77, average age 61 ± 17 years), 108 (77.1%) were classified as allergic: 61 (56.5%) as Severity I and 47 (43.5%) as Severity 11, 26 (18.6%) as intolerant and the remaining six (4.3%) as not substantiated.The standard documentation of the patients' penicillin allergies was poor - only 40 (38.6%) of either medical records or drug charts had the type of reaction and only five (3.6%) had the date of reaction. In general, penicillin allergies were poorly documented in both patients' medical records and on drug charts. Inadequate detail of reported reactions often made it difficult to assess their clinical significance. These findings prompted a recommendation that pharmacists should help to ensure accurate allergy documentation by evaluating patients and educating both patients and health care professionals.